Biodiversity of marine tardigrades from the northern coast of Portugal (Iberian Peninsula). (December 2016) - Rubal, Marcos; Veiga, Puri; Fontoura, Paulo; Santos, Erika; Sousa‐Pinto, Isabel
Abstract : Information about marine tardigrades in the Iberian Peninsula is very scarce. To improve our knowledge of this group, a sampling programme was started in 2010. The main coastal marine habitats of northern Portugal were explored. Eighteen species were found. Four species are new to science (the previously described Prostygarctus aculeatus Rubal, Veiga, Fontoura & Sousa‐Pinto, 2013 and three species of the genus Batillipes ), and another four species of the genera Batillipes, Echiniscoides, Halechiniscus and Wingstrandarctus are potentially new species. Moreover, six species ( Stygarctus bradypus Schulz, 1951; Halechiniscus greveni Renaud‐Mornant & Deroux, 1976; Styraconyx haploceros Thulin, 1942; Styraconyx sardiniae D'Addabbo Gallo, Morone De Lucia & de Zio Grimaldi, 1989; Anisonyches diakidius Pollock, 1975; and Batillipes tubernatis Pollock, 1971) were recorded in the Iberian Peninsula for the first time. Two species ( A .  diakidius and S. sardiniae ) were recorded for the Atlantic Ocean for the first time and the distribution range of S. haploceros and B. tubernatis was extended to the south. The results showed the importance of collecting information from poorly studied regions to achieve a better understanding of the biogeography of marine tardigrades. Finally, intertidal rocky shores were shown to be more diverse than other habitats, probably due to the great habitat heterogeneity.